CARING FOR PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND SOME RELATED FACTORS AT AN GIANG GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the nursing care of patients with chronic obstructive pulmonary disease and associated factors at An Giang General Hospital in 2025.Method: A cross-sectional study was conducted on 167 inpatients with obstructive pulmonary disease. Data were collected through semi-structured questionnaires and direct nursing care observation. Descriptive and correlation statistics were applied with a significance level of p < 0.05.Results: The mean age was 66.8 ± 9.7 years, with 49.1% aged ≥ 70; males accounted for 75.4%. The most common symptoms were dyspnea (89.2%), chronic cough (73.7%), and sputum production (60.5%). Effective nursing care was achieved in 80.2% of cases. Significant factors included advanced age, disease severity, and family involvement.Conclusion: The care provided to patients with chronic obstructive pulmonary disease at An Giang General Hospital has yielded positive results. Special attention should be given to elderly patients and those with severe disease.
Keywords: Chronic obstructive pulmonary disease, COPD, care, nursing, An Giang.